Correlation between Apoptosis and Histological Grade of Transitional Cell Carcinoma of Urinary Bladder - Jalali Nadoushan, Mohammadreza; Peivareh, H; Azizzadeh Delshad, A (Urology Journal, 2009)
Purpose: To evaluate the relationship between histological grade and apoptotic index (AI) in transitional cell carcinoma (TCC) of urinary bladder. Materials and Methods: Formalin-fixed and paraffin-embedded tissue blocks from 75 patients with TCC, who undergone transurethral resection (TUR) were studied. One 3-micron section was provided from each TUR samples. In one section after hematoxylin and eosin (H&E) staining, tumor grade was determined according to World Health Organization/International Society of Urology and Pathology (WHO/ISUP) criteria. The apoptotic cells were determined using a terminal deoxynucleotidyl transferase (TdT) mediated dUTP biotin nick end labeling (TUNEL) technique. Apoptotic index was then obtained as the percent of TUNEL positive cells from observations of at least 1000 cells in each section. Results: Forty-nine patients were men and 26 were women. Mean age was 56.34?9 years. Mean AI was 2.30?0.50. The relationship between grade and AI was significant (p=0.000, r=0.551); a higher grade was associated with a higher AI. Conclusion: Apoptosis index has a positive correlation with bladder TCC’s grade. Further studies are needed to better determine the effect of apoptosis index on prognosis.